Selectivity in the mechanism of action of antimicrobial mastoparan peptide Polybia-MP1 - Santos Cabrera, Marcia Perez dos [UNESP]; Broggio Costa, Sabrina Thais [UNESP]; Souza, Bibiana Monson de [UNESP]; Palma, Mario Sergio [UNESP]; Ruggiero, José Roberto [UNESP]; Neto, Joao Ruggiero [UNESP] (Springer, 2008)
Many potent antimicrobial peptides also present hemolytic activity, an undesired collateral effect for the therapeutic application. Unlike other mastoparan peptides, Polybia-MP1 (IDWKKLLDAAKQIL), obtained from the venom of the social wasp Polybia paulista, is highly selective of bacterial cells. The study of its mechanism of action demonstrated that it permeates vesicles at a greater rate of leakage on the anionic over the zwitterionic, impaired by the presence of cholesterol or cardiolipin; its lytic activity is characterized by a threshold peptide to lipid molar ratio that depends on the phospholipid composition of the vesicles. At these particular threshold concentrations, the apparent average pore number is distinctive between anionic and zwitterionic vesicles, suggesting that pores are similarly formed depending on the ionic character of the bilayer. To prospect the molecular reasons for the strengthened selectivity in Polybia-MP1 and its absence in Mastoparan-X, MD simulations were carried out. Both peptides presented amphipathic alpha-helical structures, as previously observed in Circular Dichroism spectra, with important differences in the extension and stability of the helix; their backbone solvation analysis also indicate a different profile, suggesting that the selectivity of Polybia-MP1 is a consequence of the distribution of the charged and polar residues along the peptide helix, and on how the solvent molecules orient themselves according to these electrostatic interactions. We suggest that the lack of hemolytic activity of Polybia-MP1 is due to the presence and position of Asp residues that enable the equilibrium of electrostatic interactions and favor the preference for the more hydrophilic environment.
Keywords: selectivity; cationic antimicrobial peptide; Hydrophobicity; wasp venom mastoparan; lytic activity and cooperativity; conformational analysis